A comparative test of centrifugal cream separators - Waldraven, Luther Watts (My University, 1900)
Introduction: During the month of March, 1900, a series of tests were made of two centrifugal cream separators in use at the dairy school of the Kansas State Agricultural College. The object of the tests was primarily, to determine the amount of power required to operate each separator. A secondary object was to make a more general comparison of the two machines, comparing the capacities, skim-milk tests, etc. Each machine was installed by its manufacturer. Both separators were in good order, and care was taken to test both under as nearly the same conditions as possible. The power used was measured by a Flather hydraulic transmission dynamometer, which was carefully inspected and calibrated in the College Engineering Laboratory. The constant of the dynamometer was accurately computed, which constant, multiplied by the reading of the pressure-gauge, and by the number of revolutions per minute, gave the horse-power transmitted at the instant the readings were taken. The skim-milk tests were by the Babcock test, and were made by the dairy students in charge. Owing to the fact that the students were not thoroughly familiar with the work, several of the skim-milk tests were lost, and some are incorrect.
Citation: Waldraven, Luther Watts. A comparative test of centrifugal cream separators. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Cream Separator; Equipment; Babcock Test; United States Number 1 Belt; Alpha Number 1 Belt; Theses